The Effect of Repetition Simulation after Debrief Method on Learning Satisfaction and Learning Achievement in Midwifery Students at Universitas Airlangga, Indonesia - Budi Prasetyo1,2, Wahyul Anis2 , Rize Budi Amalia2 , Dwi Izzati2 , Woro Setia Ningtyas2 , Ratna Dwi (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Simulation and debrief are one kind of learning method used in midwifery education.Repetition of the simulation (redo) after debrief is expected to improve students’ satisfaction and learningachievement. In Indonesia, the implementation of the simulation method has not been well structured andredo research is still limited.Aims: This research examined the differences between students’ satisfaction, learning achievement andimplementation time when doing the first simulation and redo after debrief in the antenatal care subject.Method: The study used a pre-experimental quantitative method that observes the level of satisfaction,learning achievement and time used when doing the first simulation and redo after the debriefing. Thesamples were 45 midwifery students using a total sampling technique. Data on students’ satisfaction levelswere obtained through the interview method with a questionnaire and the learning achievement and timewere obtained through the observation method with a checklist graph. The data of the study were analyzedusing the Wilcoxon signed ranks test.Result: There were significant differences in the level of students’ satisfaction and the learning achievementwhen doing the first simulation and redo after debrief, but there was no significant difference in the timeallocated to finish the scenario when doing the first simulation and redo after debrief.Conclusion: The Redo after debriefs simulation increases the level of students’ satisfaction and learningachievement on midwifery students in the Faculty of Medicine, Universitas Airlangga, Indonesia.